Contact effect on the current-voltage characteristic of graphene nanoribbon based schottky diode - Kiat, Wong King (American Scientific Publishers, 2015)
This paper presents the study of the current-voltage characteristic of graphene nanoribbon based Schottky diode using analytical method. The work presents a simple model to analyse the current-voltage characteristic in the function of Schottky barrier properties such as the potential barrier and the Schottky barrier lowering effect of graphene nanoribbon contact. Thermionic emission effect and tunneling effect were considered in the development of the current-voltage characteristic. By using the analytical method, the analytical model for potential barrier, Schottky barrier lowering effect and the current-voltage characteristic of graphene nanoribbon Schottky diode are presented. Based on the obtained result, it is found that the potential barrier has a quadratic relationship relative to its depletion region width. Besides that, the Schottky barrier lowering effect is dependent on the applied voltage. Both of these two parameters, the potential barrier and the Schottky barrier lowering effect are temperature dependent. The presented current-voltage model was compared with silicon Schottky diode and germanium Schottky diode which shows different contact effect when different metal and semiconductor were used for Schottky contact. Moreover a comparison study between the presented model with experimental graphene Schottky diode shows that the presented model indicates similar leaning of the current-voltage characteristic with experimental work.